Buckling‐Induced Assembly of Three‐Dimensional Tunable Metamaterials. Issue 4 (15th February 2018) - Zhou, Shiwei; Xie, Yi Min; Lin, Sen; Feng, Xi‐Qiao; Li, Qing
Abstract : Conventional metamaterials are usually confined to planar settings due to the fabrication challenges at the nanoscale. Here, we explore the shape transformation of metasurfaces into three‐dimensional metamaterials to generate some on‐demand plasmon modes which would be otherwise unachievable in two dimensions. This method is inspired by the buckling‐induced folding of a layer of metal sheet bonded to a stretchable compliant substrate in some specified regions. Two prototypes of three‐dimensional metamaterials are obtained, demonstrating the enhancement of quality factors as well as the tunability. We find the occurrence of sharp Fano resonance and the resonance mode with toroidal dipole attributed to the structural asymmetry in depth. This work provides an effective approach to practical fabrication of nanoscale metamaterials in an extra dimension that would enable a wide range of applications in the optical spectrum. Abstract : A simple method to produce 3D metamaterial operating at visible spectrum is proposed in this letter. By controlling the strain in the flexible substrate, the optical properties of the nano‐architectures can be tuned to some extent.